2000
DOI: 10.1093/chromsci/38.5.200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fluoxetine, Fluvoxamine, and Clomipramine in Pharmaceutical Formulations by Capillary Gas Chromatography

Abstract: A simple and fast capillary gas chromatographic method with flame ionization detection is proposed for the simultaneous determination of fluoxetine, fluvoxamine, and clomipramine without a prederivatization. The reported method is the first one that allows the determination of three selective serotonin reuptake inhibitors. Optimal conditions for the quantitative separation were investigated: column head pressure (80 kPa), injector and detector temperatures (260 and 250 degrees C), time and temperature for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Several instrumental methods have been proposed for the determination of FXT in pharmaceutical samples and biological fluids including liquid chromatography, [5][6][7] gas chromatography, 8,9) spectrofluorimetry, 10,11) and capillary electrophoresis. 12,13) Most of the spectrophotometric methods reported for determination of FXT involve difficult and timeconsuming extraction procedures.…”
Section: Fluoxetine (Fxt) Hydrochloride N-methyl-3-phenyl-3-[4-mentioning
confidence: 99%
“…Several instrumental methods have been proposed for the determination of FXT in pharmaceutical samples and biological fluids including liquid chromatography, [5][6][7] gas chromatography, 8,9) spectrofluorimetry, 10,11) and capillary electrophoresis. 12,13) Most of the spectrophotometric methods reported for determination of FXT involve difficult and timeconsuming extraction procedures.…”
Section: Fluoxetine (Fxt) Hydrochloride N-methyl-3-phenyl-3-[4-mentioning
confidence: 99%
“…This is quite striking because this high-boiling-point analyte typically requires very long run times and (or) lengthy derivatization steps to analyze it by conventional GC methods. 20 As a result, it is normally determined using HPLC or capillary electrophoresis. 21,22 It is also interesting to note that this analyte could also be directly analyzed in aqueous solution in the ultrashort GC column system.…”
Section: System Operating Characteristicsmentioning
confidence: 99%
“…A survey of literature revealed that spectrophotometric 3,4 , spectrofluorimetric 5,6 , electrochemical 7 , gas chromatography 8 , liquid chromatography [9][10][11] , capillary zone electrophoresis (CZE) 12 methods for determination of FH from pharmaceutical formulation and spectrophotometric [13][14][15][16][17] , linear voltametric 16 , HPLC [16][17][18] , CZE 18 methods for determination of OZ from pharmaceutical dosage form whereas HPLC [19][20][21][22] and HPTLC 21,22 methods for the simultaneous determination of FH and OZ from combined dosage forms were reported.…”
Section: Fig 1b: Olanzapine Figure 1a and B: Chemical Structures Of Flmentioning
confidence: 99%